Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.sapharm.2018.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare professionals' perceptions related to the provision of clinical pharmacy services in the public health sector: A case study

Abstract: The perception analysis performed in this study suggested that it is necessary to increase pharmacy staff in order to improve interprofessional relationships and the quality of clinical pharmacy services provision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…e model was widely used in the evaluation of various links of public health service, such as the evaluation of treatment outcomes (outcome), quality of service provision (outcome), and general practitioners training program (process). [29][30][31][32].…”
Section: Evaluation Framework and Indicatorsmentioning
confidence: 99%
“…e model was widely used in the evaluation of various links of public health service, such as the evaluation of treatment outcomes (outcome), quality of service provision (outcome), and general practitioners training program (process). [29][30][31][32].…”
Section: Evaluation Framework and Indicatorsmentioning
confidence: 99%
“…In regarding patient perceptions, the service was important because it influenced the self-perception of health (clinical and economic improvement). Medication reviews, in a variety of settings, showed positive impacts for patients, which also include economic savings in various specialties and levels of healthcare 22,43,44 . The economic improvement reported by patients is very important, given that their socioeconomic profile shows that 64.3% have low income (1 to 3 minimum wages).…”
Section: Perception Of the Medication Review With Patient Follow-upmentioning
confidence: 99%
“…Counseling, considered a professional attribute, was also a duty recognized by the health team and patients, and has been associated with improved several outcomes 15,44,58 . However, a review revealed wide variability in the components of pharmacist counseling, for there is no standard definition regarding such counseling, making it necessary to build standardized models 59 .…”
Section: Perception Of the Pharmacist Acting In Mental Healthmentioning
confidence: 99%
“…These characteristics will not only describe the distribution of respondents but will also contribute to analyzing the in luence of each character towards the perception score resulted in the study. Several factors that are known to affect medical and nurses' acceptance toward clinical pharmacy services include frequency of communication, professional culture, high workload, high turnover, strong compliance or support with medical chiefs' prescription patterns, lack of awareness on medication errors, the resistance for interprofessional collaboration as well as lack of knowledge about clinical pharmacists' roles (de León-Castañeda et al, 2019;Li et al, 2014).…”
Section: Characteristics Of Respondentsmentioning
confidence: 99%
“…A study in ive private hospitals in Pakistan revealed that the expectation for the pharmacist as a drug expert was not in line with the real condition where most interaction with the pharmacist was only related to drug availability and alternatives. The lack of knowledge of a clinical pharmacy role from other health professionals can also contribute to the weak collaboration with the pharmacist (de León-Castañeda et al, 2019;Khan et al, 2014). Therefore, as mentioned above, continuous professional development which consists of not only pharmaceutical expertise but also communication skills are essential for developing signi icant professional relationship and collaboration for the sake of the patients.…”
Section: In Luence Of Characteristics Toward Perception On Clinical Pmentioning
confidence: 99%